(untitled) (Global Journal of Science Frontier Research, 2019)
Twenty-first century Physics is in crisis indicated by theoretical inconsistency between Relativity Theory (RT) and Quantum Mechanics (QM) and empirically undetectable "darkmatter" and "dark-energy". a leading candidate ’Theory of Everything’ (TOE) is the ’Computational Unified Field Theory’ (CUFT) shown capable of unifying between RT and QM, discards "dark-matter", "dark-energy" and challenges "Big-the Bang" Model and revises "Material-Causal" assumption underlying RT’s ’Einstein’s Equations’. The CUFT revises QM and RT asembedded within a ’Universal Computational Formula’ (UCF). A complete unification of "space", "time", "energy" and "mass" is postulated as arising from a singular ’Universal Computational Principle’ (UCP), associated with a new ’A-Causal Computation’ (ACC) Paradigm which also replicates and revises fundamental tenets of General Relativity and provides a new satisfactory Paradigm for 21st century Physics